2016
DOI: 10.1007/s00590-016-1751-5
|View full text |Cite
|
Sign up to set email alerts
|

Anterior shoulder stabilization by Bristow–Latarjet procedure in athletes: return-to-sport and functional outcomes at minimum 2-year follow-up

Abstract: IV, retrospective study-Case series with no comparison group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 25 publications
1
81
0
6
Order By: Relevance
“…9 Although the arthroscopic Bankart repair shows similar comparative values of reluxations in some case series, Lartajet still contains better clinical results and lower dislocation and subluxation rates after long-term follow-up, and it offers greater safety for athletes to resume their activities. 4,3,13,14 For strikers, central-midfielders, defenders and full-backs, the instability can cause major problems for their careers. The residual pain, ROM loss and positive seizure are factors that can lead to fear of new dislocations due to falls and physical contact, reduced professional performance and inefficiency in throw-ins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Although the arthroscopic Bankart repair shows similar comparative values of reluxations in some case series, Lartajet still contains better clinical results and lower dislocation and subluxation rates after long-term follow-up, and it offers greater safety for athletes to resume their activities. 4,3,13,14 For strikers, central-midfielders, defenders and full-backs, the instability can cause major problems for their careers. The residual pain, ROM loss and positive seizure are factors that can lead to fear of new dislocations due to falls and physical contact, reduced professional performance and inefficiency in throw-ins.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several techniques have been proposed to restore stability, function and prevent the development of glenohumeral instability, especially when it comes to athletes with high demand and professionals. 4 The arthroscopic Bankart repair is a therapeutic option with excellent results in non-athletes but higher failure rates in practitioners of professional contact sports athletes. 5 Thus, the Lartajet procedure is a viable option for arthroscopic repair failure, in bipolar lesions and when there is a high probability of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several authors have reported success following bone transfer procedures involving the glenohumeral joint in contact athletes. 1 , 2 , 10 , 14 Beranger et al 2 reported that all of the 47 athletes examined in their study returned to sports after Latarjet-Bristow, although those individuals who practiced overhead sports were less likely to return to preinjury levels. The Latarjet procedure is popularly performed in Europe for treatment of recurrent anterior shoulder instability in contact athletes, while the procedure is less frequently performed in the United States.…”
Section: Discussionmentioning
confidence: 80%
“…External rotation in the abduction position is noticeably limited by both reconstructions as a result of scar formation within the subscapularis muscle, which is transversely divided during the procedure (44). This restriction makes the procedure less desirable in overhead-throwing athletes, because external rotation is an essential motion during overhead throwing (45). The procedure is contraindicated in patients with instability resulting from a subscapularis tear because at the end-range arm position, the subscapularis muscle is one of the most important anterior stabilizers of the shoulder (41).…”
Section: Bristow-latarjet Proceduresmentioning
confidence: 99%